2013 IEEE Sixth International Conference on Cloud Computing 2013
DOI: 10.1109/cloud.2013.12
|View full text |Cite
|
Sign up to set email alerts
|

A Declarative Environment for Automatic Performance Evaluation in IaaS Clouds

Abstract: One of the main challenges faced by users of infrastructure-as-a-service (IaaS) clouds is the difficulty to adequately estimate the virtual resources necessary for their applications. Although many cloud providers offer programatic ways to rapidly acquire and release resources, it is important that users have a prior understanding of the impact that each virtual resource type offered by the provider may impose on application performance. This paper presents Cloud Crawler, a new declarative environment aimed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 11 publications
0
36
0
Order By: Relevance
“…Cloud has gathered pace, as most enterprises are moving toward the agile hosting of multi-tier applications in public clouds, many researchers have focused on three different research directions: 1) updating application architecture to move from legacy systems to clouds [3], 2) evaluating different clouds' functional and non-functional attributes for allowing cloud users to correctly make a decision on which cloud to host applications [2,4,7,8], and 3) efficiently orchestrating virtual appliances in a cloud, which may also include negotiations with cloud users. While some highly related previous work has principally focused on estimating rudimentary cloud capabilities using benchmarks [8] and automated performance testing [9],our approach focuses on the precise characterization of application capabilities in a cloud infrastructure.…”
Section: Related Workmentioning
confidence: 99%
“…Cloud has gathered pace, as most enterprises are moving toward the agile hosting of multi-tier applications in public clouds, many researchers have focused on three different research directions: 1) updating application architecture to move from legacy systems to clouds [3], 2) evaluating different clouds' functional and non-functional attributes for allowing cloud users to correctly make a decision on which cloud to host applications [2,4,7,8], and 3) efficiently orchestrating virtual appliances in a cloud, which may also include negotiations with cloud users. While some highly related previous work has principally focused on estimating rudimentary cloud capabilities using benchmarks [8] and automated performance testing [9],our approach focuses on the precise characterization of application capabilities in a cloud infrastructure.…”
Section: Related Workmentioning
confidence: 99%
“…The importance of estimating cloud configuration has been mentioned in (Cunha, 2013) as well, and they have proposed an approach to collect the estimates from public clouds. However, in their approach, users must need a help from application expert to deploy the application and collect estimates.…”
Section: Related Workmentioning
confidence: 99%
“…In this regard, many researchers have focused on three (Chauhan, 2011), (ii) evaluating different clouds' functional and non-functional attributes for informed decision on which cloud to host applications (Jayasinghe, 2011;Huang, 2010;Calheiros, 2011;Jayasinghe, 2011;Cunha, 2013), and (iii) efficient orchestration of virtual appliances in a cloud (Keahey, 2008), which may also include negotiations with users (Venugopal, 2009). This paper complements these different directions by enabling recommendation of cloud configuration to suit application requirements.…”
Section: Related Workmentioning
confidence: 99%
“…The results showed that the prototype is functional and able to measure the metrics of the target environment. Cunha et al (2013) [13] create a programmable environment to evaluate the performance of IaaS.The environment allows several performance test parameters to be set up, such as the number of providers and their features. A performance evaluation for two levels of workload was conducted using an environment consisting of IaaS EC2 and Rackspace machines.…”
Section: Related Workmentioning
confidence: 99%